1986
DOI: 10.1083/jcb.103.6.2729
|View full text |Cite
|
Sign up to set email alerts
|

The effect of neutrophil migration on epithelial permeability.

Abstract: Abstract. To reach an inflammatory lesion, neutrophils must frequently traverse the epithelium of an infected organ. Whether the actual migration of neutrophils alters the epithelial permeability is unknown. Through the use of an in vitro model system it was possible to directly determine the effect of neutrophil emigration on the transepithelial electrical resistance of the monolayer. Human neutrophils (5 x 106 cells/ml) were placed in the upper compartment of a combined chemotaxis/resistance chamber and stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(39 citation statements)
references
References 32 publications
0
39
0
Order By: Relevance
“…Since these results predict that the basement membrane of venules surrounding an inflamed site are undergoing active perforation, it is tempting to speculate that the leakage of lipoproteins, fibrinogen, and erythrocytes into inflamed sites in vivo reflects the imperfect masking of matrix defects by the overlying endothelium (72,73). Finally, it should be stressed that conclusions regarding the status of the subendothelial basement membrane are quite distinct from recent reports demonstrating the ability of migrating neutrophils to alter transcellular electrical resistance (74,75). The electrical measurements only reflect the "tightness" of intercellular occluding junctions to small ions, and changes in electrical resistance occur independently of alterations in basement membrane integrity (13).…”
Section: Discussionmentioning
confidence: 44%
“…Since these results predict that the basement membrane of venules surrounding an inflamed site are undergoing active perforation, it is tempting to speculate that the leakage of lipoproteins, fibrinogen, and erythrocytes into inflamed sites in vivo reflects the imperfect masking of matrix defects by the overlying endothelium (72,73). Finally, it should be stressed that conclusions regarding the status of the subendothelial basement membrane are quite distinct from recent reports demonstrating the ability of migrating neutrophils to alter transcellular electrical resistance (74,75). The electrical measurements only reflect the "tightness" of intercellular occluding junctions to small ions, and changes in electrical resistance occur independently of alterations in basement membrane integrity (13).…”
Section: Discussionmentioning
confidence: 44%
“…Small numbers of neutrophils can transmigrate without any change in permeability, as measured by electrical resistance and macromolecular flux (6,15,94,120), and although larger numbers of transmigrating neutrophils (especially if activated) induce increased epithelial permeability, this can be transient and reversible (24,93,120,122). This suggests that there are mechanisms by which tight junctions are opened and closed to allow for paracellular neutrophil transmigration without marked and permanent increased permeability or damage to the epithelium.…”
Section: Regulated Disassembly Of Tj By Intracellular Signaling Pathwmentioning
confidence: 99%
“…Studies of PMN transepithelial migration have largely focused on this nonphysiologically directed migration for technical reasons (Evans et al, 1983;Cramer et al, 1986;Milks et al, 1986;Nash et al, 1987;Migliorisi et al, 1988;Parkos et al, 1991). However, we have also recently shown that, while the efficiency of transmigration does vary depending on the direction in which PMN cross monolayers, in several qualitative ways transmigration is similar in both directions (i.e., ability of transmigration to proceed, specific chemotactic gradients required, and CDllb/18 dependence) .…”
Section: Ifn-'y Modulates Pmn Transepithelial Migration In the Apicalmentioning
confidence: 99%